2012
DOI: 10.1103/physrevlett.108.086803
|View full text |Cite
|
Sign up to set email alerts
|

Collective Nature of the Reentrant Integer Quantum Hall States in the Second Landau Level

Abstract: We report an unexpected sharp peak in the temperature dependence of the magnetoresistance of the reentrant integer quantum Hall states in the second Landau level. This peak defines the onset temperature of these states. We find that in different spin branches the onset temperatures of the reentrant states scale with the Coulomb energy. This scaling provides direct evidence that Coulomb interactions play an important role in the formation of these reentrant states evincing their collective nature.The second Lan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
73
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(86 citation statements)
references
References 52 publications
12
73
1
Order By: Relevance
“…2.19 shows four reentrant states per spin branch, interposed by different FQHS. They appear at partial filling˜= 0.29, 0.43, 0.57, and 0.70, in agreement with previous publications [116][117][118]. That raises the question whether the reentrant states in the second Landau level are of equal nature as the bubble phases in higher levels.…”
Section: Reentrant States In the 2nd Landau Levelsupporting
confidence: 80%
See 1 more Smart Citation
“…2.19 shows four reentrant states per spin branch, interposed by different FQHS. They appear at partial filling˜= 0.29, 0.43, 0.57, and 0.70, in agreement with previous publications [116][117][118]. That raises the question whether the reentrant states in the second Landau level are of equal nature as the bubble phases in higher levels.…”
Section: Reentrant States In the 2nd Landau Levelsupporting
confidence: 80%
“…Indeed, besides the IQHE transport behavior, other similarities to the bubble phases in higher Landau levels are present, such as sharp and hysteretic features in the -characteristics [116] as well as pinning modes in microwave absorption [120]. In addition, it has been demonstrated that the onset temperatures of the RIQHS in the second Landau level scale with the Coulomb energy, which highlights the importance of electron-electron interactions for the origin of these states [118]. However, also discrepancies to the bubble phases in higher Landau levels are evident.…”
Section: Reentrant States In the 2nd Landau Levelmentioning
confidence: 99%
“…Besides the FQHS at ν = 5/2, we also observe strong FQHSs at ν = 7/3 and 11/5, and there are indications of developing FQHSs at ν = 8/3, and 14/5. Furthermore, in Fig.2a we notice three peaks in R xx at B = 1.10, 1.04, and 0.98 T. We associate these peaks with precursors at temperatures above the onset temperature of the reentrant integer quantum Hall states R2a, R2b, and R2c, respectively 80 .…”
Section: Magnetoresistance Datamentioning
confidence: 88%
“…It has been predicted that the less studied FQHE state at ν = 2 + 1/3 = 7/3 could possess exotic quasiparticles in which composite fermions are dressed by a cloud of neutral excitations [20]. Since FQHE liquids as well as bubble and stripe phases can serve as ground states, the N=1 LL is home to a striking competition between quantum phases [21].The interplay of anisotropic phases with FQHE liquids in the second LL has been studied by introduction of in-plane magnetic fields [3,[22][23][24][25]. These experiments provide evidence that anisotropic smectic-or nematic-like phases with broken full rotational invariance coexist with quantum Hall liquids [26][27][28][29][30].…”
mentioning
confidence: 99%
“…It has been predicted that the less studied FQHE state at ν = 2 + 1/3 = 7/3 could possess exotic quasiparticles in which composite fermions are dressed by a cloud of neutral excitations [20]. Since FQHE liquids as well as bubble and stripe phases can serve as ground states, the N=1 LL is home to a striking competition between quantum phases [21].…”
mentioning
confidence: 99%